The Spatial-Temporal Evolution Characteristics and Driving Factors of the Green Utilization Efficiency of Urban Land in China - Zhang, Lijuan; Yu, Yuzhu; Chen, Yongheng (Frontiers in Environmental Science, 2022)
With the acceleration of urbanization, the urban land area of different spatial scales in China continues to increase, the urban land use efficiency is relatively low, and there are great regional differences. Land is an important material carrier for human production, life, and socio-economic activities. Reasonable measurement of the green utilization efficiency of urban land (Glande) has important theoretical and practical significance for the realization of urban land green use and the formulation of related policies. In this context, based on the publicly available data of 282 China’s cities at prefecture-level and above from 2009 to 2019, this study measures Glande with the Super-SBM (DEA) model. After analyzing the spatio-temporal evolution characteristics of Glande, we employ the spatial dynamic Durbin model to analyze the spatial spillover effects. The results showed that: (1) Glande in China shows a fluctuating and rising trend, but it has not reached the effective state; (2) the agglomeration characteristics of urban land green use efficiency are significant, and from a regional point of view, it shows the pattern of western > eastern > central; (3) Glande is the result of the interaction of many factors. In the future, measures should be taken according to urban policies and local conditions, and differential measures should be taken to improve Glande.